PERKEMBANGAN PEMIKIRAN FILSAFAT ISLAM MODERN (SEBUAH TINJAUAN UMUM) - Wardani, Wardani (Jurnal Ilmu Ushuluddin, 2015)
This article is aimed to deal with the development of Islamic philosophy in modern era in many countries, both in the East and the West, in the world commonly, and in Indonesia particularly. Islamic philosophy in this era has grown through four stages. Firstly, at the beginning of 19th century, when the modernization in Muslim countries has been initiated by Jamâl al-Dîn al-Afghânî. Secondly, since 19th until 20th century, when some orientalists among Jews have studied the Islamic philosophy. Thirdly, post-World War II, when the Islamic philosophy has become the concern of the Eastern and Western scholars. Fourthly, the golden age of Islamic philosophy has come, since 20th century hitherto, when the bordes has fused in the sense that both Western and Eastern scholars have collaborated in jointintellectual agenda to study of Islamic philosophy. The Study of Islamic philosophy in Indonesia, in particular, has passed three stages of development; firstly, in 1960-1970s, the stage of consolidation has begun through efforts carried out by Harun Nasution to cultivate rational thought in the mind of Indonesian Moslems; secondly, in 1980-1990s, the stage of institutionalization has begun when the department of theology and philosophy at the Faculty of Ushûl al-Dîn at Syarif Hidayatullah State Institute for Islamic Studies in Jakarta has been initiated in 1982; finally, since 1990 hitherto, the stage of functionalization, when the Islamic philosophy has been studied in Islamic universities, and even functionalized to solve many problems.